The Communal Lyric: Poetry in Devotional and Oppressed Communities - Yacoub, Michael N. (AUC Knowledge Fountain, 2025)
This thesis investigates the interaction between lyric and community; it asks what a communal lyric is, how it functions, and to what ends. In Chapter One, I compare Jonathan Culler’s performative model of lyric with the theory of Takhyīl as expounded by Arab philosopher-critics al-Farabi, Ibn Sina, and al-Qartajanni to argue that a communal lyric is a form of audience-oriented public discourse distinguished by formal features that prompt the poem’s (re-)iteration and establish an interpersonal relationship with the audience in order to influence them and make shareable value claims about the world. In Chapters Two and Three I provide close-reading analyses of selected poems to show two possible relationships that the communal lyric can establish between speaker and audience: apprenticeship and acknowledgement. In Chapter Two, I analyse selected psalms and ibtihālāt (supplications), poems by George Herbert and John Donne, as well as Al-Busiri’s Burda (Mantle Ode) to show how poems function liturgically in devotional communities by situating the audience in alignment with the speaker’s perspective as apprentices in faith through their distinctive use of temporality and modes of address. In Chapter Three, I analyse five poems by Claude McKay, Dennis Brutus, Eavan Boland, Keorapetse Kgositsile, and Mahmoud Darwish, each of which is embedded in a context of racial or colonial oppression, to show how poems of oppressed communities function differently for different audiences: for members of the oppressed community, they act through apprenticeship, while for non-members, and by performing a rhetorical argument, they confront their audience demanding that audience members acknowledge an experience in which they cannot partake. In the conclusion, I trace apprenticeship and acknowledgement in two contemporary communal lyrics, Shervin Hajipour’s “Baraye” (2022) and Refaat Al-Areer’s “If I Must Die” (2023), to show the wide-reaching impact of the communal lyric on today’s world.